Emergency dealing with snakebites - Ghaemmaghami A. (Iran University of Medical Sciences, 1988)
EXTRACTAnyone who may one day be faced with an injured snake bitten and be forced to take care of him. If this person does not know how to treat these patients consciously and quickly, may cause further injury or even death in them. Notice a snake- bitten history: He had gone with his friends for circulation, when he saw a snake, try to take it. But his hands being bitten by snake. His friends kill snake and after that transfer him and snake to the nearest emergency. If you were at the emergency center, what do you do for these patient? Can you properly identify venomous snakes in your area? Do you know emergency new methods to deal with these cases?